2018
DOI: 10.1002/hbm.24236
|View full text |Cite
|
Sign up to set email alerts
|

Distinct neural substrates for visual short‐term memory of actions

Abstract: Fundamental theories of human cognition have long posited that the short-term maintenance of actions is supported by one of the "core knowledge" systems of human visual cognition, yet its neural substrates are still not well understood. In particular, it is unclear whether the visual short-term memory (VSTM) of actions has distinct neural substrates or, as proposed by the spatio-object architecture of VSTM, shares them with VSTM of objects and spatial locations. In two experiments, we tested these two competin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 95 publications
(116 reference statements)
1
25
1
Order By: Relevance
“…These studies predominantly focused on the WM storage of the pure action information embedded in BMs. For instance, WM can retain three to four individual actions that are stored independently from location, color, shape, and color-shape binding (e.g., Cai et al, 2018;Gao, Bentin, & Shen, 2015;Lu et al, 2016;Shen, Gao, Ding, Zhou, & Huang, 2014;Wood, 2007Wood, , 2011; storing actionrelated binding is resource-demanding (e.g., Ding et al, 2015;Liu, Lu, Wu, Shen, & Gao, 2019;Lu, Ma, Zhao, Gao, & Shen, 2019). To isolate pure action information, the tested BM stimuli were in fact collected from a single actor in almost all WM studies of BM (e.g., the BMs from the widely used Vanrie & Verfaillie, 2004, database were acquired from one actor).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies predominantly focused on the WM storage of the pure action information embedded in BMs. For instance, WM can retain three to four individual actions that are stored independently from location, color, shape, and color-shape binding (e.g., Cai et al, 2018;Gao, Bentin, & Shen, 2015;Lu et al, 2016;Shen, Gao, Ding, Zhou, & Huang, 2014;Wood, 2007Wood, , 2011; storing actionrelated binding is resource-demanding (e.g., Ding et al, 2015;Liu, Lu, Wu, Shen, & Gao, 2019;Lu, Ma, Zhao, Gao, & Shen, 2019). To isolate pure action information, the tested BM stimuli were in fact collected from a single actor in almost all WM studies of BM (e.g., the BMs from the widely used Vanrie & Verfaillie, 2004, database were acquired from one actor).…”
Section: Introductionmentioning
confidence: 99%
“…However, each BM in our daily life is produced by a distinct person, carrying a dynamic motion signature that informs of one's identity (e.g., Barclay, Cutting, & Kozlowski, 1978;Beardsworth & Buckner, 1981;Cutting & Kozlowski, 1977;Loula et al, 2005;Runeson & Frykholm, 1983, 1986Stevenage, Nixon, & Vince, 1999;Troje, Westhoff, & Lavrov, 2005). Although agent identity and action are processed by different neural substrates (e.g., Cai et al, 2018;Downing, Jiang, Shuman, & Kanwisher, 2001;Downing, Peelen, Wiggett, & Tew, 2006;Puce & Perrett, 2003;Urgesi, Candidi, Ionta, & Aglioti, 2007), recent studies have implied that there is an intimate relation between action and BM identity (Balas & Pearson, 2017;Pilz & Thornton, 2017;Simhi & Yovel, 2017). For instance, Pilz and Thornton (2017) found that body motion affects the processing of identity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, as compared to object-WM, BM-WM only holds a maximum of 3–4 BM stimuli (Smyth et al, 1988; Wood, 2007; Shen et al, 2014). 1 Later neuroimaging studies further uncovered the neural substrates of BM-WM by showing that the mirror neuron system (MNS) plays a pivotal role in retaining BM in WM (Gao et al, 2013; Lu et al, 2016; Cai et al, 2018). Recent studies have also begun to explore issues such as the development of BM-WM (He et al, 2019), the influence of other social information (e.g., social interaction and emotion) on BM-WM capacity (Ding et al, 2017; Guo et al, 2019), BM-related binding in WM (Wood, 2008; Poom, 2012; Ding et al, 2015; Gu et al, 2019), the representation format of BM in WM (Vicary and Stevens, 2014; Vicary et al, 2014), and the frame of reference for remembering BM (Wood, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, since the storage of WM involves a series of cognitive operations, WM may have a tight relation with Gf, regardless of the stimuli type. Two recent functional magnetic resonance (fMRI) studies (Lu et al, 2016; Cai et al, 2018) found that, in addition to the MNS, the superior and inferior parietal lobule (SPL and IPL) and bilateral prefrontal cortex, which contribute to general cognitive processes (e.g., Todd and Marois, 2004; Xu and Chun, 2006; Barbey et al, 2013), also play a role in retaining BM in WM. Therefore, it is also possible that BM-WM capacity not only correlates to social ability, but also links to general cognitive ability.…”
Section: Introductionmentioning
confidence: 99%